Potential of Mimosa pudica leaf in the treatment of ulcerative colitis in rat (Bangladesh Journal of Pharmacology, 2018)
The aim of present investigation was to validate its folk use in the treatment of ulcerative colitis in the rat model. Sprague Dawley rats were divided into nine groups with six animals in each group. The rats received seven days of pretreatment with chloroform, ethyl acetate or ethanolic extract of Mimosa pudica. For induction of ulcerative colitis, rats were administered with 2 mL of 4% acetic acid solution intrarectally. Ulcer index, macroscopical study of the colon, myeloperoxidase and malondialdehyde levels in colon tissue and blood, and histopathology of the colon tissue were studied. Intrarectal instillation of acetic acid caused increased ulcer index, colonic myeloperoxidase and malondialdehyde. Pretreatment with M. pudica ethanolic extract (400 mg/kg) significantly lowered the ulcer index, colonic myeloperoxidase and malondialdehyde as compared with the standard drug prednisolone. The present investigation demonstrates that the ethanol extract of M. pudica leaf is effective in the treatment of ulcerative colitis.Video Clip of Methodology:Embedding or block making: 24 sec  Click to watchTissue processing: 19 sec   Click to watchSection cutting: 33 sec   Click to watch